Psychological Contract Fulfilment and Turnover Intentions: Do Millennials view differently? - Abro, Elsa; Akbar, Waqar; Sarhan, Purab (International Journal of Psychosocial Rehabilitation, 2020)
The relation of exchange between employer and employee for organizations and researchers can be analyzed through studying Psychological contract. This relationship has never been challenged before by other generations the way it is today; mostly because Millennials unlike their precursor generations increasingly inhabit the total workforce in organization. The present study aims to examine the impact of psychological contract fulfilment on turnover intention with the mediating role of affective commitment among the millennials in the context of Pakistan. 342 Millennials working in private sector of Karachi Pakistan participated in the study. Using Partial Least Square Structural Equation Modeling, the results reveal that three psychological contract fulfilment contents namely Autonomy, Job security and Task Description have significant impact on turnover intentions of millennials. However, other contents of psychological contract fulfilment are insignificant. Further, the study finds the significant mediating role affective commitment between two psychological contract fulfilment contents and turnover intentions of Millennials. The study is useful for HR professional and policy makers to gain insights on psychological contract from millennials perspective in context of Pakistan. The study also suggests the future avenue for Sociologist Psychologist and Organizational researchers who are interested to understand the perspective of Millennials.